Le récit plantigrade (sur Madame Bovary) - Guy Larroux (Flaubert: Revue Critique et Génétique)
A plantigrade narrative: this is not a new narratological category but a way to understand the remarkable predilection of Flaubert’s tale for the low, the earth, the surfaces treaded upon by individuals in every circumstance of life. The outcome is a particular approach to the tangible world that justifies the expression “down to earth”, commonly used against realistic art. The order of the portrait is equally altered by it, as though Flaubert interpreted literally and in his own way the expression “de pied en cap” (from foot to head, that English reverses: “from head to foot”). On observing the variously shoed population in Madame Bovary, we can appraise the importance of the foot, the shoe, and are surprised by the constant attention paid to the connections from below. We also understand how Flaubert’s intention to “paint the below and the above” is precisely and topologically expressed in the novel.